Primary pulmonary paraganglioma: Report of two cases with one case showing cytokeratin positivity - Pasricha, Sunil; Kumar, Ankur; Jajodia, Ankush; Darlong, Laleng; Mehta, Anurag (Indian journal of cancer, 2025)
Abstract Primary pulmonary paraganglioma (PPP) is a rare tumor, with few cases described in the literature. Here, we report two cases of PPP, one of which shows cytokeratin (CK) positivity, along with a literature review. In the first case, a 76-year-old male patient presented with a right-lung peribronchial mass, while in the second case, a 53-year-old male, presented with a right middle lobe mass. In both cases, the guided biopsy revealed a similar morphology comprising a tumor with polygonal cells in a back-to-back nested pattern, showing strong immunoexpression with synaptophysin and chromogranin. In the first case, a heterogenous immunoexpression of CK was observed, which was an unusual finding. In small biopsy specimens, PPPs with an aberrant CK expression can be misdiagnosed as pulmonary carcinoids or non-small cell lung carcinoma, which have distinct prognostic and therapeutic implications. Both cases underwent lobectomy, and the findings were confirmed on the resection specimen. The presented cases highlight the role of diligent histomorphological examination, coupled with clinico-radiological input and a judicious immunohistochemistry panel, to avoid erroneous interpretation and management.